Development of a structural model for the adoption of industry 4.0 enabled sustainable operations for operational excellence - Gupta, Sumit; Prathipati, Basai; Dangayach, Govind Sharan; Rao, Posinasetti Nageswara; Jagtap, Sandeep (MDPI, 2022)
In the current competitive scenario, SMEs need to adopt advanced technology in order to comprehend the dynamics of Industry 4.0 and the sustainable operations for operational excellence. The present study discusses the relationship between Industry 4.0 with sustainable operations and operational excellence. A research model is proposed and assessed through structural equation modelling (SEM). The current research shows that if SMEs adopt Industry 4.0 practices and the use of advanced robotics in order to minimize human intervention, as well as smart logistics that react to changes in production capacity, virtual reality and dynamic simulation techniques, then SMEs can significantly achieve sustainability in manufacturing operations. Furthermore, this study will help companies to attain an operational excellence with greater efficiency and productivity. Therefore, SMEs need to focus on sustainable manufacturing practices.
Keywords: Industry 4.0; sustainable operations; operational excellence; small and medium enterprises (SMEs); digitalization